Analysis of Physicians’, Pharmacists’, and Nurses’ Attitudes Toward the Use of Computers to Access Drug Information - Shumway, J. M.; Jacknowitz, A. I.; Abate, M. A. (Methods of Information in Medicine, 1990)
The appropriate utilization of computerized drug information systems is widely recognized as an area of concern by health care professionals. For this reason, attitudes of health care professionals in office-based practices toward computer-based drug information were examined. Sixty individuals in five different practice settings completed an attitude instrument. Of the 36 items categorized into five attitudinal categories, the answers to six items (in three distinct categories) were found to be statistically different among physicians, nurses, and pharmacists. These differences indicate that physicians and nurses are less knowledgeable about the benefits that can be obtained through the use of computerized information resources and, consequently, are more skeptical concerning the role of computer information systems in reducing the costs and improving the quality of health care. Of interest as well was the finding that pharmacists felt more strongly than physicians and nurses that computer information systems would readily fit into their daily work routine.
Keywords: Attitudes to Computers; Drug Information